Mapeando a Situação Educacional no estado de Sergipe - Parente, Juliano Mota; Parente, Cláudia da Mota Darós [UNESP] (My University, 2010)
This article examines historical and legal aspects of educational policy in Brazil, presenting the main challenges for the consolidation of the new National Education Plan, currently under construction. From this, the article focuses on the description of some educational indicators, describing the educational reality in the state of Sergipe. The study focuses on indicators for early childhood education, to primary education and teacher training, showing historical deficits in basic education. In describing data on education in the state of Sergipe, contextualizing it within the framework and illustrates some national educational policies implemented in the state. As a result of the study is intended to show the importance of research into the educational policy in the state of Sergipe, in order to contribute to improving the quality of educational provision.

O presente artigo analisa aspectos histórico-legais da política educacional brasileira, apresentando os principais desafios para a consolidação do novo Plano Nacional de Educação, em construção. A partir disso, o artigo concentra-se na descrição de alguns indicadores educacionais, mapeamento a realidade educacional do estado de Sergipe. O estudo focaliza dados relativos à educação infantil, ao ensino fundamental e à formação de professores, mostrando déficits históricos na Educação Básica. Por meio desse panorama, pretende-se contribuir para o conhecimento das condições atuais da educação no estado, bem como para a visualização de problemas e desafios. Como resultado do estudo, pretende-se mostrar a importância de pesquisas no âmbito da política educacional no estado de Sergipe, de modo a contribuir para a melhoria da qualidade da oferta educacional.